2018
DOI: 10.29252/ijrm.16.7.429
|View full text |Cite
|
Sign up to set email alerts
|

The vitamin D level in umbilical cord blood in premature infants with or without intra-ventricular hemorrhage: A cross-sectional study

Abstract: Background:Intra-ventricular hemorrhage (IVH) is acute cerebral complications of premature infants which may lead to the long-term problems.Objective:According to the role of vitamin D in the stability of the blood vessels, the present study was carried out in order to compare the vitamin D level in the premature infants with or without IVH.Materials and Methods: This cross-sectional study was carried out on 180 premature infants in the Ghaem Hospital, Mashhad, Iran 97 infants without IVH (53.9%) and 83 with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The incidence of vitamin D deficiency has been reported at 30% to 88% in infants as well as mothers worldwide. [20][21][22][23][24][25][26] In a study in Iran, 552 mothers and infants were examined for serum vitamin D levels and the results showed that 66% of the mothers and 93% of the newborns had vitamin D deficiency. 27 Our findings demonstrated a high prevalence of vitamin D deficiency among Iranian mothers and newborns, which is consistent with the mentioned study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of vitamin D deficiency has been reported at 30% to 88% in infants as well as mothers worldwide. [20][21][22][23][24][25][26] In a study in Iran, 552 mothers and infants were examined for serum vitamin D levels and the results showed that 66% of the mothers and 93% of the newborns had vitamin D deficiency. 27 Our findings demonstrated a high prevalence of vitamin D deficiency among Iranian mothers and newborns, which is consistent with the mentioned study.…”
Section: Discussionmentioning
confidence: 99%
“…19 Respiratory distress syndrome (RDS), retinopathy of prematurity (ROP) and cerebral hemorrhage are other common newborn problems in which vitamin D is involved. 20,21 The relationship between vitamin D and TTN has not been studied widely; accordingly, this research was done to evaluate the serum levels of vitamin D in TTN newborns and also their mothers and compare them to a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D values < 30 nmol/L were considered as vitamin D deficiency. Vitamin D deficiencies were divided into severe deficiency (25-hydroxyvitamin D < 10 ng/mL), moderate deficiency (10 -20 ng/mL), and mild (suboptimal) deficiency (20.10 -30 ng/mL) (12).…”
Section: Methodsmentioning
confidence: 99%
“…In a study of 44 infants born before the 29th week of gestation, the average vitamin D level of the umbilical cord blood was 33.8 ng/mL in 41 survived neonates and 30.4 ng/mL in 3 dead neonates, and there was a significant difference between the two groups in the vitamin D level (14). Several studies have shown that respiratory distress, intraventricular hemorrhage, retinopathy of prematurity, and infections are more common in newborns with vitamin D deficiency (12,13). On the other hand, the problems regarding neonatal morbidity and mortality have important effects.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation